Application of E-Planning as a form of Technology-Based Regional Planning System in Nias Barat Regency - Halawa, Yohannes Asarudy (Jurnal Insinyur Profesional, 2022)
West Nias Regency Government in implementing integrated Good Governance initiatives from local government to the central government, which is accomplished through Electronic Government for Good Governance. The purpose is to maximize the use of information and communication technology infrastructure in collaboration with all agencies. In West Nias, excellent governance is being implemented. Qualitative descriptive was the research method used in this study. Data collection techniques were carried out by interview and documentation. Data analysis was carried out using theory, data sources, and triangulation methods. The result of the study related to the implementation of e-planning in West Nias Regency is the implementation of the West Nias Regent's Regulation Number 66 of 2017 concerning the Management of Electronic-Based Regional Development Planning Applications in the West Nias Regency Government. This Regent's Regulation is a follow-up to efforts to integrate the use of information technology in government activities, particularly those related to development planning. The ongoing E-Planning application is still in the web presence stage because when viewed in its application the E-Planning website does not provide an interactive space for the public. The initiation process, provision of instruments, socialization, and preparations have been carried out, with limited network capacity so that in its implementation there are still some problems such as server errors that often occur, overcapacity access, causing operators waiting for login. Human resources who are proficient in programming are not accommodated properly. With all the problems faced, the government of West Nias Regency has been considered quite agile in solving problems and obstacles in the implementation of E-Planning. Aspects of Technology which is part of E-Learning, the response of the West Nias Regency Government is quite fast when an error occurs on the server. In terms of bureaucratic or technical aspects, the West Nias Regency Government will increase the capacity of the internet network at certain times so that it is hoped that there will be minimal obstacles when entering data. If there is an urgent problem but the Bappeda of West Nias Regency cannot handle it alone, then coordination is carried out with the Medan City Government to find a solution to the problem at hand. In the Human Resources Aspect, the West Nias Regency Government does not immediately release the operator independently but provides technical guidance as expected.